Antioxidant Activity, Dietary Fiber, Colour Analysis (L,a,b) and Viscosity of Kiwi–Kepok Banana Fruit Leather with Adding Moringa oleifera - Habsari, Windi; Rahmah, Latifahtur; Nanda Hiranyo, Emmanuel Adwitya (Journal of Applied Food Technology, 2026)
This study aimed to evaluate the effect of Moringa oleifera leaf incorporation on the functional and physical characteristics of kiwi and kepok banana fruit leather. Five formulations were developed by adding 0 to 8 g of Moringa powder per 100 g of fruit puree. The results demonstrated that dietary fiber content significantly increased from 3.11 to 3.65 g/100 g with higher Moringa concentrations, while antioxidant activity improved as evidenced by a reduction in IC₅₀ values from 262.28 to 125.43 ppm. The viscosity of the puree also rose from 913.44 cP to 1106.96 cP, indicating enhanced textural consistency and structural integrity. Conversely, the color parameters (L*, a*, b*) showed a notable shift, with increasing Moringa addition resulting in darker and greener hues attributed to chlorophyll pigments. These findings suggest that Moringa oleifera fortification effectively improves the nutritional and textural qualities of fruit leather, offering a viable approach for producing plant-based functional snacks that appeal to health-conscious consumers.